PELAKSANAAN HAK ASUH ANAK SETELAH TERJADINYA PERCERAIAN - Umul Khair (STIH Putri Maharaja, 2020)
Based on law, children under the age of ten, should be passed into their mother. Whereas for children over the age of ten have a right to choose, even though, in reality, they will be more is taken care of by their father. This study aims to find out how the implementation of child custody after the divorce occurred in the Jopang Manganti kenagarian?. In addition, the study was made to find out what obstacles arose in the implementation of child custody after the divorce took place in Jopang Manganti? As well as how is the solution to overcome the obstacles in the implementation of child custody after the divorce took place in Jopang Manganti? This study uses a sociological juridical approach which concludes that the implementation of child custody after the divorce in the Jopang Manganti religion is in fact incompatible with the decision of the religious court with the constraints. These constraints include: Lack of a sense of responsibility of the mother, the mental condition of the mother who is not ready to face divorce, lack of religious knowledge of the mother. The researcher also recommends that the solution to this obstacle is to give the mother an understanding of the responsibility that the child is entrusted by God. Another solution is to provide an understanding that not every divorce has a negative impact, increasing the understanding of religion that God has predestined divorce.